Cover Feature: Improving Lithium‐Ion Diffusion Kinetics in Nano‐Si@C Anode Materials with Hierarchical MoS2 Decoration for High‐Performance Lithium‐Ion Batteries (ChemElectroChem 7/2021). Issue 7 (17th March 2021) - Ye, Xiongbiao; Gan, Chuanhai; Huang, Liuqing; Qiu, Yiwei; Xu, Ying; Huang, Liuying; Luo, Xuetao
Abstract : The Cover Feature shows the synthesis procedure of an urchin‐like Si@C@MoS2 anode material for lithium‐ion batteries. This material has the potential to be the anode material for next‐generation lithium‐ion batteries. Future battery technology can reduce pollution and make our world more beautiful. More information can be found in the Aricle by X. Ye et al .